Full-Length Transcriptome Analyses of Genes Involved in Triterpenoid Saponin Biosynthesis of Psammosilene tunicoides Hairy Root Cultures With Exogenous Salicylic Acid - Su, Lingye; Li, Shufang; Qiu, Hanhan; Wang, Hongfeng; Wang, Congcong; He, Chunmei; Xu, Mingfeng; Zhang, Zongshen (Frontiers in Genetics, 2021)
Triterpenoid saponins constitute a diverse class of bioactive compounds in medicinal plants. Salicylic acid (SA) is an efficient elicitor for secondary metabolite production, but a transcriptome-wide regulatory network of SA-promoted triterpenoid saponin biosynthesis remains little understood. In the current study, we described the establishment of the hairy root culture system for Psammosilene tunicoides, a triterpenoid saponin-producing medicinal herb in China, using genetic transformation by Agrobacterium rhizogenes. Compared to controls, we found that total saponin content was dramatically increased (up to 2.49-fold) by the addition of 5 mg/L SA in hairy roots for 1 day. A combination of single-molecule real-time (SMRT) and next-generation sequencing (Illumina RNA-seq) was generated to analyze the full-length transcriptome data for P. tunicoides, as well as the transcript profiles in treated (8 and 24 h) and non-treated (0 h) groups with 5 mg/L SA in hairy roots. A total of 430,117 circular consensus sequence (CCS) reads, 16,375 unigenes and 4,678 long non-coding RNAs (lncRNAs) were obtained. The average length of unigenes (2,776 bp) was much higher in full-length transcriptome than that derived from single RNA-seq (1,457 bp). The differentially expressed genes (DEGs) were mainly enriched in the metabolic process. SA up-regulated the unigenes encoding SA-binding proteins and antioxidant enzymes in comparison with controls. Additionally, we identified 89 full-length transcripts encoding enzymes putatively involved in saponin biosynthesis. The candidate transcription factors (WRKY, NAC) and structural genes (AACT, DXS, SE, CYP72A) might be the key regulators in SA-elicited saponin accumulation. Their expression was further validated by quantitative real-time PCR (qRT-PCR). These findings preliminarily elucidate the regulatory mechanisms of SA on triterpenoid saponin biosynthesis in the transcriptomic level, laying a foundation for SA-elicited saponin augmentation in P. tunicoides.